Investigation on Constraints and Recommended Context Aware Elicitation for IoT Runtime Workflow - Kumar, V. Suresh; Kulkarni, Sanjeev; Mukkapati , Naveen; Singhal, Abhinav; Tiwari, Mohit; David, D. Stalin (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Various technological and application challenges arise in the advancement of Internet of Things. Apart from Design and Deployment, Security also falls as a primary challenge to overcome. Device Management is becoming more complex as numerous network services to be handled. Inter-device communication for technical aspects appears to be underappreciated. There is a critical necessity to include this area's requirements and challenges. By abstracting data models and operations and expressing them using semantics, M2Mcommunication and interoperability and may be made simple. A thorough investigation of the foregoing is preparing the way for various approaches. Along with Semantics, a high-level language construct is suggested that can enable run-time workflow construction. Things Markup Language is the name of the concept (TML).